2010
DOI: 10.1139/a10-017
|View full text |Cite
|
Sign up to set email alerts
|

Growth and reproduction of vascular plants in polluted environments: a synthesis of existing knowledge

Abstract: Identification of factors explaining diversity in plant responses to industrial pollution is crucial for predicting fates of polluted ecosystems. Meta-analysis based on 203 publications demonstrated that plants growing near point polluters showed similar decreases in characters reflecting growth (-13.1%) and reproduction processes (-8.5%). In herbaceous plants, root growth was reduced, while aboveground biomass did not change, because the decrease in leaf size was compensated by an increase in leaf number. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 78 publications
2
13
0
3
Order By: Relevance
“…In urban areas, organisms are exposed to pollutants such as nitrogen dioxide (NO 2 ), nitric oxide (NO), ozone (O 3 ), sulfur dioxide (SO 2 ), heavy metals, and fine particulates, which could negatively affect their fitness and limit plant growth (Kuttler , Zvereva et al. , Bell et al. , Calfapietra et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In urban areas, organisms are exposed to pollutants such as nitrogen dioxide (NO 2 ), nitric oxide (NO), ozone (O 3 ), sulfur dioxide (SO 2 ), heavy metals, and fine particulates, which could negatively affect their fitness and limit plant growth (Kuttler , Zvereva et al. , Bell et al. , Calfapietra et al.…”
Section: Discussionmentioning
confidence: 99%
“…), a recent meta‐analysis concluded that the overall pollution effect on growth and reproduction of plants is negative, in particular for annual herbaceous plants (Zvereva et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of abiotic stress experienced by plants are commonly quantified by decreases in leaf size (Farooq, Wahid, Kobayashi, Fujita, & Basra, 2009;Zvereva, Roitto, & Kozlov, 2010) and in specific leaf area (SLA; Casper, Forseth, Kempenich, Seltzer, & Xavier, 2001;Marron et al, 2003). In each sample, we measured the length of leaf lamina (with a ruler, to the nearest 1 mm) and SLA in five randomly selected leaves.…”
Section: Insect Herbivory and Plant Stressmentioning
confidence: 99%
“…A decrease in the root-shoot ratio is a general response of herbaceous plants to pollutants; however, no quantitative data on the root-shoot ratio exist for mature trees (Zvereva et al, 2010). Birch seedlings showed higher biomass allocation to roots when growing in polluted relative to unpolluted soils (Bojarczuk et al, 2002), while an application of acid rain and heavy metals to birch seedlings during two months caused no statistically significant changes in the root-shoot ratio (Koricheva et al, 1997).…”
Section: Biomass Reductionsmentioning
confidence: 99%